Stochastic short-term maintenance scheduling of GENCOs in an oligopolistic electricity market - Fotouhi Ghazvini, Mohammad Ali; Canizes, Bruno; Vale, Zita; Morais, Hugo (Applied energy, 2013)
► Decision making under uncertainty. ► Stochastic Mixed Integer Quadratic Programming applied to short-term maintenance scheduling. ► Outage scheduling in Oligopolistic electricity markets. ► Generation companies maintenance scheduling. In the proposed model, the independent system operator (ISO) provides the opportunity for maintenance outage rescheduling of generating units before each short-term (ST) time interval. Long-term (LT) scheduling for 1 or 2years in advance is essential for the ISO and the generation companies (GENCOs) to decide their LT strategies; however, it is not possible to be exactly followed and requires slight adjustments. The Cournot-Nash equilibrium is used to characterize the decision-making procedure of an individual GENCO for ST intervals considering the effective coordination with LT plans. Random inputs, such as parameters of the demand function of loads, hourly demand during the following ST time interval and the expected generation pattern of the rivals, are included as scenarios in the stochastic mixed integer program defined to model the payoff-maximizing objective of a GENCO. Scenario reduction algorithms are used to deal with the computational burden. Two reliability test systems were chosen to illustrate the effectiveness of the proposed model for the ST decision-making process for future planned outages from the point of view of a GENCO.